Anatomy of the forelimb musculature and ligaments of Psittacus erithacus (Aves: Psittaciformes) - Razmadze, Daria (J Anat, 2018)
Parrots (order Psittaciformes) are a rather homogeneous group of birds that can be easily distinguished by the notably modified morphology of the skull and hindlimb. Detailed description of the forelimb morphology in these birds has never been provided, though parrots are often used as model objects in flight studies. Parrots are also considered the closest living relatives of the perching birds (Passeriformes), and thus knowledge of the wing morphology in Psittaciformes is important for understanding the evolution of the locomotor apparatus on the way to the most speciose group of birds. Here we provide a comprehensive illustrated description of the wing morphology (musculature and ligaments) of the African grey parrot (Psittacus erithacus) and compare it with several closely related taxa of the high clade Eufalconimorphae and more distantly related outgroups (based on personal dissections and literature data). We note a general similarity of the wing musculature between P. erithacus and Falconidae. A number of features common with the outgroup Columbidae supports a generally plesiomorphic structure of the forelimb in parrots as compared with the Passeriformes. Nevertheless, the wing of the Psittaciformes displays a series of structural (likely autapomorphic) modifications, which can be explained in terms of adaptations for flight with vertical body. An analysis of the anatomical data for parrots (ratio of wing elevators and highly unusual development of the M. supracoracoideus), which is based on the current experiment‐based knowledge of the flapping flight in birds, allows us to hypothesize that parrots are able to produce useful aerodynamic force during the upstroke, which is also known for pigeons and hummingbirds. This supposed ability of vertical flight and the zygodactyl foot together link the origin of parrots with the dense (likely tropical) forests.